Elimination of virulent strains (aprV2) of Dichelobacter nodosus from feet of 28 Swiss sheep flocks: A proof of concept study. (October 2016) - Greber, D.; Bearth, G.; Lüchinger, R.; Schuepbach-Regula, G.; Steiner, A.
Highlights: The aprV2/aprB2 PCR is a useful diagnostic tool for sheep with foot lesions. Complete elimination of aprV2 strains of D. nodosus from feet of sheep is possible. Six footbaths in weekly intervals are a protective factor for being aprV2 -positive. The number of weekly footbaths is positively correlated with the clinical prevalence. The number of weekly footbaths is not correlated with the flock size. Abstract: Virulent ovine footrot caused by Dichelobacter nodosus is an endemic disease worldwide. It is associated with severe pain, impaired animal welfare and economic losses. The competitive real-time PCR for the differentiation of virulent aprV2 and benign aprB2 strains of Dichelobacter nodosus provides an objective, rapid and sensitive diagnostic tool for footrot surveillance, especially as it enables early detection of subclinical carriers of virulent strains. The aim of this study was to evaluate the feasibility of complete elimination of Dichelobacter nodosus strains carrying the aprV2 gene from sheep flocks. The treatment protocol was based on careful removal of loose and severely overgrown claw horn, weekly stand-in foot baths of the entire flock for 10 min per sheep, using a 10% zinc sulphate disinfectant solution, clinical and PCR follow-up and isolation or culling of non-responders. Dichelobacter nodosus strains carrying the aprV2 gene were successfully eliminated from the feet of the sheep of all 28 flocks (100%) participating in the study within 6–19 weeks of weekly foot bathing. A strong correlation between the length of time for weekly foot bathing to eliminate the virulent strains and the within-flock prevalence of clinical footrot at the beginning was observed (rho, 0.68; P < 0.001). A statistically significant correlation was not detected between flock size and the length of time for weekly foot bathing (rho, 0.28; P = 0.14), or the prevalence of clinical footrot at study commencement (rho, −0.04; P = 0.82), respectively. In conclusion, a complete elimination of Dichelobacter nodosus strains carrying the aprV2 gene in sheep flocks was possible with a protocol based on careful trimming, weekly stand-in foot baths, and identification of infection using a specific PCR-test and isolation or culling of non-responders.